2014
DOI: 10.3109/14767058.2014.955966
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolomics of bronchopulmonary dysplasia (BPD): preliminary data at birth suggest it is a congenital disease

Abstract: These preliminary results seem to be promising for the identification of predictor's biomarkers characterizing the BPD condition. These data may suggest that BPD is probably the result of an abnormal development (respiratory bud, vascular tree, hypodysplasia of pneumocytes) and could be considered a congenital disease (genetics plus intrauterine epigenetics). Early identification of infants at the greater risk of developing BPD may allow a targeted approach for reducing disease severity and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 41 publications
1
49
0
Order By: Relevance
“…Conversely, the high taurine urinary level in the group of dead babies may be considered an index of cell necrosis and death due to hypoxia. closely comparable behavior to that found in this study, confirming the key role of this metabolite in predicting clinical outcome (44). The trend over time of lysine is similar to that of lactic acid and taurine.…”
Section: Discussionsupporting
confidence: 72%
“…Conversely, the high taurine urinary level in the group of dead babies may be considered an index of cell necrosis and death due to hypoxia. closely comparable behavior to that found in this study, confirming the key role of this metabolite in predicting clinical outcome (44). The trend over time of lysine is similar to that of lactic acid and taurine.…”
Section: Discussionsupporting
confidence: 72%
“…14−16 The noninvasive collection of newborn urine and subsequent ease to address large cohorts, compared to newborn blood, makes it a particularly interesting biofluid in the present context. This has indeed been recognized in reports on the newborn urinary impact of prematurity, 17−20 IUGR, 21−23 large for gestational age (LGA), 22,23 GDM, 3 asphyxia, 11,24,25 respiratory distress syndrome (RDS), 24 meconium aspiration syndrome (MAS), 24 bronchopulmonary dysplasia, 26 IEM, 27 neonatal sepsis, 28 postnatal bacterial, 19 cytomegalovirus, 29 and fungal 30 infections. Most of these studies have considered relatively small cohorts (up to ca.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Comparing the urinary metabolic profiles at birth of preterm neonates, Fanos et al found five discriminant metabolites: lactate, taurine, trimethylamine-N-oxide (TMAO), myo-inositol (which increased in BPD patients), and gluconate (which was decreased) [14]. The increase in urinary lactate in the BPD group may represent a process of anaerobic respiration.…”
Section: Respiratory Distress Syndrome and Bronchopulmonary Dysplasiamentioning
confidence: 99%